Implementation of the Principle of Ultimum Remedium through a Restorative Justice Approach in Handling Minor Persecution in the North Sumatra Police - Siregar, Rahmad; Zuliah , Azmiati; Maysara, Andi (Tasyri' : Journal of Islamic Law, 2026)
The handling of minor assault offenses within the Indonesian criminal justice system is grounded in the principle of ultimum remedium, which positions criminal punishment as a measure of last resort. In line with the development of the restorative justice paradigm, the police are granted discretion to resolve certain cases through non-litigation mechanisms focused on restoration. This article examines victim protection, the implementation of the ultimum remedium principle, and the obstacles encountered in the application of restorative justice in handling minor assault cases at the North Sumatra Regional Police. This study employs an empirical legal research method combined with statutory and conceptual approaches. The findings indicate that, in principle, the application of restorative justice at the North Sumatra Regional Police reflects the ultimum remedium principle; however, its implementation continues to face normative, structural, and cultural challenges that affect the effectiveness of victim protection and legal certainty.